2011
DOI: 10.1002/bjs.7566
|View full text |Cite
|
Sign up to set email alerts
|

Cohort study of patients with adrenal lesions discovered incidentally

Abstract: In this prospective cohort study 6·6 per cent of patients with an AI had surgery and benign hormone-producing tumours were verified in 3·1 per cent. Repeat CT and hormone evaluation after 2 years did not increase the sensitivity for diagnosis of malignant or hormone-producing tumours.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
22
0
3

Year Published

2012
2012
2016
2016

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(28 citation statements)
references
References 24 publications
3
22
0
3
Order By: Relevance
“…In agreement with the other contemporary reports [32,36] we found a low prevalence (1.6%) of primary adrenal carcinoma among patients with AI. The observed percentage may however underestimate the true frequency of the condition as some large tumours with invasion of adjacent tissues or distant metastases at the initial radiological examination may have been directly referred to surgical departments thus escaping prior endocrinological evaluation.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…In agreement with the other contemporary reports [32,36] we found a low prevalence (1.6%) of primary adrenal carcinoma among patients with AI. The observed percentage may however underestimate the true frequency of the condition as some large tumours with invasion of adjacent tissues or distant metastases at the initial radiological examination may have been directly referred to surgical departments thus escaping prior endocrinological evaluation.…”
Section: Discussionsupporting
confidence: 93%
“…Earlier studies have reported higher proportion of hypersecreting tumours but some of them suffer from different forms of bias such as including patients from surgical and oncology series, excluding patients with small tumours or patients with non-functioning tumours, or analyzing small number of patients. A recent prospective study in Sweden including unselected patients from radiological departments estimated the prevalence of hormonally active tumours at 3.1% [32]. A meta-analysis deliberately excluding studies with potential selection bias also confirmed the previous overestimation of the prevalence of hypersecreting lesions by showing that they represent less than 10% of AIs [36].…”
Section: Discussionmentioning
confidence: 67%
See 1 more Smart Citation
“…A systematic review of 14 studies assessing the natural course of 1410 patients with apparently benign, nonfunctioning adrenal incidentalomas (3) and 10 additional cohort studies were included (21,40,44,46,146,147,160,161,162,163,164,165,166,167 The quality of evidence from these studies was judged moderate or low. Selection criteria were often not reported, the duration of follow-up was heterogeneous across studies (medians ranging from 19 to 90 months) and the completeness of follow-up was difficult to assess.…”
Section: Natural Course Of Apparently Benign Adrenal Incidentaloma (Rmentioning
confidence: 99%
“…[2][3][4] The appropriate management-surgical vs medical-continues to be debated. 5 However, what has been established is that even in the setting of mild cortisol excess, though insufficient to instigate the typical findings of Cushing's syndrome, does predispose patients to metabolic and cardiovascular sequelae, including insulin resistance, type 2 diabetes, obesity and dyslipidemia.…”
mentioning
confidence: 99%